Pembelajaran Daring di Masa Pandemi Covid-19 di Madrasah Diniyah Takmiliyah Awaliyah - Nida Nur Afifah; Masykur Mansyur; Abdul Kosim (Universitas Islam Madura, 2022)
Abstract This study aims to describe the implementation of online learning in Madrasah diniyah takmiliyah, especially at Madrasah Diniyah Takmiliyah Miftahussa'adah III. And to describe the problems during online learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Miftahussa'adah III. This study uses a qualitative method. The type of qualitative research that is appropriate to this research is a case study. The data collection technique of this research is by observation, interview, and document study. Due to the impossibility of the situation, data collection was carried out online. However, this does not reduce the validity of the data obtained and the researcher tries to make the data obtained as detailed as possible. Based on the results of observations during the learning process and interviews with the madrasah, principals and teachers, it can be concluded as follows. (1) It can be seen that the implementation of online learning at Madrasah Miftahussa'adah III has been carried out quite well. The school and parents work well together in this online learning process. This is the key to successful online learning during this pandemic. (2) Constraints and problems in the learning process are divided into two parts, namely students and teachers. However, from each obstacle, a solution has been found along with getting used to doing online learning.